PENGARUH LIVE STREAMING DAN CONTENT MARKETING PADA PLATFORM TIKTOK TERHADAP IMPULSE BUYING PADA BRAND ELZATTA - Shodiq, Aliffatur Akbar; Wijayanti, Rena Feri; Murtiyanto, Rizky Kurniawan (Politeknik Negeri Malang, 2025)
The rapid advancement of digital technology has transformed consumer behavior, particularly by increasing impulsive purchasing on social media platforms such as TikTok. One strategic response to this shift is the use of live streaming and content marketing, approaches adopted by the local brand Elzatta through TikTok Shop. However, the effectiveness of these strategies remains limited due to the small number of viewers during live broadcasts and content that lacks distinctiveness. This study examines the influence of live streaming and content marketing on the impulsive buying behavior of TikTok users. A quantitative design with a descriptive approach was employed. Data were collected through purposive sampling from one hundred TikTok users who had viewed Elzatta’s live sessions and interacted with its content. The analysis involved multiple linear regression along with validity, reliability, classical assumption tests, t-tests, and F-tests. The findings show that both live streaming and content marketing have a positive and significant effect on impulsive buying. The coefficient of determination (R²) of 0.709 indicates that the model explains a substantial portion of the variance. The study suggests that audience engagement needs improvement; therefore, the use of moderators and consistent communication in Indonesian is recommended to enhance responsiveness and encourage impulsive purchases.